ESTIMATION OF POSSIBILITY OF TYRE UTILIZATION PRODUCTS USAGE AS ALTERNATIVE FUEL - Grytsenko, A.; Vnukova, N.; Pozdniakova, Ye.; Гриценко, А. В.; Внукова, Н. В.; Позднякова, Е. И.; Позднякова, Є. І. (Харьковский национальный автомобильно-дорожный университет, 2015)
It was shown that without additional processing neither solid nor liquid products of tire pyrolysis can be used in practice. The purification methods of pyrolysis liquid used for installations are proposed. They offer to use liquid products as alternative diesel fuel, solid products - as alternative fuel for energy installations.
ОЦЕНКА ВОЗМОЖНОСТИ ИСПОЛЬЗОВАНИЯ ПРОДУКТОВ УТИЛИЗАЦИИ ШИН В КАЧЕСТВЕ АЛЬТЕРНАТИВНОГО ТОПЛИВА
ОЦІНКА МОЖЛИВОСТІ ВИКОРИСТАННЯ ПРОДУКТІВ УТИЛІЗАЦІЇ ШИН ЯК АЛЬТЕРНАТИВНОГО ПАЛИВА
Keywords: worn tyre recycling; slag; alternative fuel; pyrolysis; утилизация шин; пиролизный шлак; альтернативное дизельное топливо; утилізація шин; піролізний шлак; альтернативне дизельне паливо